Sex-specific changes to androgen receptor content following exercise and its influence on skeletal muscle adaptions - Hatt, Aidan (My University, 2022)
The androgen hormone is responsible for the growth of secondary sex characteristics in humans, such as skeletal muscle. Upon an exercise stimulus, the androgen receptor (AR) plays a crucial role in transmitting the androgenic signal to the nucleus which upregulates transcription of target genes related to growth of skeletal muscle. AR content has been implicated in the hypertrophic response between high and low responders following resistance exercise training (RET) in males. Little is known of the impact of AR expression on acute skeletal muscle damage and whether AR may influence the adaptive response to RET in females. This study aimed to investigate acute changes to AR content following a single bout of muscle damage-inducing exercise as well as sex differences during skeletal muscle repair and hypertrophy. A skeletal muscle biopsy from the vastus lateralis was obtained from 26 healthy, young males (n=13) and females (n=13) at baseline and 48 hours following a single bout of 300 eccentric contractions of the quadriceps. Subsequently, participants performed whole-body RET 4 times a week for 10 weeks, followed by a final skeletal muscle biopsy under resting conditions. Females had greater AR mRNA than males at baseline (~53%) and post-damage (~126%; p<0.05) while AR protein content increased in both sexes similarly following a single bout of eccentric exercise (p<0.05). Damage- and RET-induced satellite cell response was associated with percent change in AR protein content in a sex-specific manner (p<0.05). RET-induced percent change in nuclear AR content was ~17% greater in males compared to females (p<0.05). Interestingly, following RET, males experiencing the highest percent change in myofibre cross sectional area (CSA) exhibited greater changes in nuclear-associated AR protein content compared to females with the highest percent change in CSA. Collectively, AR protein content is elevated following acute eccentric exercise and 10 weeks of RET. Findings from this study suggests that males are more reliant on AR-related mechanisms than females to induce skeletal muscle hypertrophy following RET.
Sex-based differences in the androgen receptor response to exercise
Keywords: androgen receptor; skeletal muscle; exercise; sex-based differences